2019
DOI: 10.1101/868885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using nonthermal plasma treatment to improve quality and durability of hydrophilic coatings on hydrophobic polymer surfaces

Abstract: Low surface energy substrates, which include many polymers in medicine/industry, present challenges toward achieving uniform, adherent, durable coatings, thus limiting intended coating function. Examples include hydrophobic polymers such as polypropylene, polyethylene, polytetrafluoroethylene, and polydimethylsiloxane. These inert materials are used in various biomedical implants due to favorable bulk properties despite perhaps unfavorable surface properties. The capability to coat such materials holds great v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We herein used both in silico and in vitro measurements to predict and confirm the relative affinity of the selected drugs for β-CD or the base polymer without inclusion complex formation, dextran (Figures 1 and 2). Previous studies have demonstrated using cyclodextrin monomers polymerized into larger macrostructures such as coatings, disks, and particles in order to delay drug release by achieving a high concentration of affinity-binding sites [27,30,31,37,44,45]. The release results herein show differences in the loading efficiencies (Figure 3), release rates ( Figure 4), and cumulative amounts of drug release ( Figure 5) which may inform the future use and design of local drug delivery depots.…”
Section: Discussionmentioning
confidence: 84%
“…We herein used both in silico and in vitro measurements to predict and confirm the relative affinity of the selected drugs for β-CD or the base polymer without inclusion complex formation, dextran (Figures 1 and 2). Previous studies have demonstrated using cyclodextrin monomers polymerized into larger macrostructures such as coatings, disks, and particles in order to delay drug release by achieving a high concentration of affinity-binding sites [27,30,31,37,44,45]. The release results herein show differences in the loading efficiencies (Figure 3), release rates ( Figure 4), and cumulative amounts of drug release ( Figure 5) which may inform the future use and design of local drug delivery depots.…”
Section: Discussionmentioning
confidence: 84%
“…To maximize pCD coating adherence and stability, PP substrates were placed in a 4" diameter x 8" length quartz reaction chamber of a Branson/IPC Model #1005-248 Gas Plasma Cleaner and treated with nonthermal plasma (500 mTorr, 50 W, 13.56 MHz) using an inlet gas mixture of argon bubbled through water (Ar/H2O) 81,83 . PP substrates were treated for a fixed 10 min duration within 1 h of pCD coating application or direct biofoulant exposure (for plasmatreated bare PP controls).…”
Section: Plasma Cleaning and Activation Of Pp Substrate Surfacesmentioning
confidence: 99%
“…In this study, polymerized CD (pCD) was applied as a coating for polypropylene (PP), chosen as a model substrate material because of its susceptibility to uncontrolled biofouling in medical [70][71][72][73][74] and industrial [75][76][77][78][79][80] applications. Given the low surface energy of olefin polymers, PP substrates were treated with nonthermal plasma to enhance pCD coating uniformity and adherence 81 . We hypothesized that pCD coatings would deter protein adsorption, cell adhesion, and bacterial attachment to PP substrates, in a manner dependent on crosslinking.…”
Section: Introductionmentioning
confidence: 99%